The straight truth about online learning in the Straits: An investigation into the nature of education in a rural and remote region of Newfoundland and Labrador - Mulcahy, Dennis; Barbour, Michael K.; Lahiri, Minakshi (Australian and International Journal of Rural Education, 2016)
This paper reports on a naturalistic research project that was conducted in response to the educational concerns of the coastal rural communities of Labrador Straits. The research project investigated the current provision of education available to the children and the youth of these communities and found that due to declining population, changing demographics, lack of qualified teaching staff in the region and several other interrelated factors, there was an increased reliance on online learning in the small rural schools of the Straits as well as other rural regions of the province.